PELAKSANAAN LAYANAN MEDIASI OLEH GURU BIMBINGAN DAN KONSELING TERHADAP PESERTA DIDIK YANG BERSELISIH DI MTsN LEMBAH GUMANTI KABUPATEN SOLOK - Framika, Rita - (Bimbingan dan Konseling, 2014)
This research is background of there are dispute that ongoing between educationparticipant by invite the education participant from another school to fight, and the peace effortthat is doing by teacherâs program not give result. This research intent to describe theimplementation of mediation services by counselor toward education participant that quarrelrefers from planning, implementation, evaluation, the results of evaluation analysis and follow-upmediation service. The kind of this research is qualitative that have characteristic of descriptive.The informant of this research is: three counselor and three education paticipant. The instrumentof this research is interview. This data is experiment by doing data triagulation and analyze bydata reduction. The results show that : 1) Planning of mediation service is that counselor makeobservation, data processing, questionnaire, obtain information from homeroom, joining in thecounselors, the education participant that have quarrel, and the eduation participant that see thefitting. Then meet the education participant in counseling guide is room. 2) The implementation ofmediation service is the education participantis collected in counseling guide is room, to be fair,create an atmosphere conducive, dynamic, and suggest the education participant to forgive eachother. 3) The evaluation carried aut during ongoing services by using evaluation aspects ofunderstanding, comfort, action and make an assessment as soon, short-term assessment, and longtermassessment. But there are also counselor that not evaluate. 4) In analyzing the results of theevaluation there are also counselor not evaluate. 5) Follow-up services of mediation known thatcounselor revise the education participant. However, there are also counselor not carry aut afollow-up mediation services.